STUDI ETNOBOTANI TUMBUHAN OBAT BERBASIS PENGETAHUAN LOKAL DI DESA SELOLIMAN KECAMATAN TRAWAS KABUPATEN MOJOKERTO JAWA TIMUR - Nurrosyidah, Iif Hanifa; Riya, Milu Asri; Ma’ruf, Alfian Fachruddin (Jurnal Riset Kefarmasian Indonesia, 2020)
Indonesia is the country with the second largest biodiversity after Brazil, where 20,000 species of medicinal plants in which 1,000 species have been documented and 300 species have been used as traditional medicine. Seloliman is a village located on the slopes of Mount Penanggungan, Trawas District, Mojokerto Regency, East Java. The people of Seloliman village still depend on nature, most people still use natural materials for treatment and daily needs. Therefore in this research ethnobotany study and identification of medicinal plants based on local knowledge will be conducted in Seloliman Village, Trawas District, Mojokerto Regency, East Java. The study was conducted by exploring the potential of the community as a place of ethnobotany research with open observation and interview methods. The technique for selecting informants is based on information from local residents or village heads who are most aware of medicinal plants. Collecting data on medicinal plants used for traditional medicine through structured interviews. Data recorded are local names, Latin names, family names, ways of obtaining, parts of plants used, diseases treated, and how they are used. Furthermore, each type of plant used is documented. Based on the results of research conducted is the type of plant used for treatment varies greatly, the plant parts used are mostly the leaves (57%), flowers (10%), and the rest are the stem, bark, rhizome, roots, flowers, fruit and seeds. Sources of plants used are mostly cultivated plants (46%), wild (30%), wild and cultivated (17%) and bought on the market (7%). While the way to use it is mostly boiled. Most of the Seloliman village community, Trawas Subdistrict, Mojokerto Regency, East Java have been influenced by outside cultures, so that their local knowledge about plants used in medicine needs to be further explored in order to be preserved. There are only two speakers (traditional healers) in the village of Seloliman who still hold the tradition related to treatment using natural materials.